Artemisia annua - a plant cure for malaria (bis) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
Advice and support on cultivation, harvesting and post-harvest handling for farmers who are growing Artemisia annua.